2016
DOI: 10.1515/vzoo-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Tropical and Holarctic Ants in Late Eocene Ambers

Abstract: Based on representative collections, the ratio of tropical and Holarctic ant species in Priabonian (Late Eocene) Baltic, Bitterfeld (Saxonian), Danish and Rovno ambers is analyzed for the first time. In surveyed representative collections of Baltic amber, the ratios of Holarctic and tropical ant species are from 1.1 to 1.5; with 10 Holarctic and 9 tropical species (out of 31) in the PIN-964 collection, and 9 and 5 species (out of 29) in the Giecewicz collection; the ratio in the representative collection of Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 17 publications
3
54
0
Order By: Relevance
“…Th e absence of this genus in the Baltic amber of the Gdańsk Bay can be explained by climatic factors, as well as the absence in this amber of the equally easily identifi able myrmicine genus Fallomyrma Dlussky et Radchenko. Th e latter genus is very common in Danish amber (6.9 % of all ants: Perkovsky, 2011) and much more abundant and diverse than previously believed in Rovno amber, in which one-third of all myrmicines belong to four species of this genus (Perkovsky, 2016).…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Th e absence of this genus in the Baltic amber of the Gdańsk Bay can be explained by climatic factors, as well as the absence in this amber of the equally easily identifi able myrmicine genus Fallomyrma Dlussky et Radchenko. Th e latter genus is very common in Danish amber (6.9 % of all ants: Perkovsky, 2011) and much more abundant and diverse than previously believed in Rovno amber, in which one-third of all myrmicines belong to four species of this genus (Perkovsky, 2016).…”
mentioning
confidence: 94%
“…Earlier it was found that in the Baltic amber, Holarctic ant species clearly prevail not just in terms of the share of their specimens (by 9.8 to 19.6 times), but also by the number of species (Perkovsky, 2016). In Bitterfeld amber, Holarctic ant species are somewhat less numerous than tropical ones, but their specimens are 6 times more numerous than tropical ones (Perkovsky, 2016).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…(Archibald and Farrell, 2003;Archibald et al 2013;Szwedo, 2012;Szwedo and Kania, 2015;Wolfe et al, 2016). Palaeoclimatic and palaeoecological interpretations result in many questions regarding the variability of Baltic amber forest(s) habitats and environments (e.g., Alexeev and Alexeev, 2016;Perkovsky, 2016;Sadowski et al, 2016aSadowski et al, , 2016bSchmidt et al, 2016;Alexeev, 2017). However, it is probable that dry and open habitats, as e.g., sparse and open forests or low vegetation areas with a few resiniferous trees or at least on borderland with amber producing trees, were present in the area and at time of the Baltic amber deposit alimentation (Kohlmann-Adamska 2001; Szwedo, 2012;Szwedo and Drohojowska, 2015).…”
Section: Palaeoenvironmentsmentioning
confidence: 99%